Finite line contact stiffness under elastohydrodynamic lubrication considering linear and nonlinear force models. (June 2020) - Tsuha, Natália Akemi Hoshikawa; Cavalca, Katia Lucchesi
Abstract: The aim of this study is to analyze the stiffness of finite line contact under elastohydrodynamic lubrication (EHL) with linear and nonlinear force approximations. The numerical solution of the finite line contact is compared with experimental results of optical interferometry. Four types of profiles are evaluated: non-profiled roller, crowned roller, dub-off profile and logarithmic profile. For each type of roller, the geometry values vary in order to identify the behavior of the reduced contact force parameters. The results of the force model showed good correspondence with the numerical solution of the EHL contact. Highlights: Study of stiffness of finite line contact under elastohydrodynamic lubrication. Comparison with experimental results of optical interferometry in literature. Different roller profiles evaluated: non-profiled, crowned, dub-off and logarithmic. Recommendations of linear and nonlinear reduced force models application.